Biological Evaluation of Ferrocenyl Olefins: Cancer Cell Growth Inhibition, ROS Production, and Apoptosis Activity. Issue 3 (3rd February 2016) - Sun, Aijing; Lin, Junsheng; Pi, Chao; Xu, Ruian; Cui, Xiuling
Abstract : The antiproliferative effects of various ferrocenyl olefins were evaluated against the cell lines MCF‐7 (human breast cancer cells), DLD‐1 (human colon adenocarcinoma cells), HUVEC (human umbilical vein endothelial cells), and A549 (human lung carcinoma cells), using the MTT test. IC50 values were determined. Compounds8, 9, 11, and12 with high antiproliferative activity were tested for their reactive oxygen species (ROS) production, and cell cycle analysis was performed on A549 cells. The results show that these compounds might perform their antiproliferative activity through inducing ROS generation, apoptosis induction, and cell cycle arrest. Abstract : The antiproliferative effects of various ferrocenyl olefins were evaluated against MCF‐7, DLD‐1, HUVEC, and A549 cells. Compounds 8, 9, 11, and 12 showed high antiproliferative activities. These compounds might exert their antiproliferative effects through inducing reactive oxygen species generation, apoptosis induction, and cell cycle arrest.